The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/cmi.13176
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ESCRT‐III complex in controlling integrity of the Salmonella ‐containing vacuole

Abstract: Intracellular pathogens need to establish specialised niches for survival and proliferation in host cells. The enteropathogen Salmonella enterica accomplishes this by extensive reorganisation of the host endosomal system deploying the SPI2-encoded type III secretion system (SPI2-T3SS). Fusion events of endosomal compartments with the Salmonella-containing vacuole (SCV) form elaborate membrane networks within host cells enabling intracellular nutrition. However, which host compartments exactly are involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 75 publications
(90 reference statements)
1
18
0
Order By: Relevance
“…Expression constructs encoding cytoplasmic mKate-tagged EqtSM and EqtSol were created by PCR amplification followed by cloning into NheI and AgeI sites of mKate-LifeAct-7 (Addgene #54697), thereby replacing the LifeAct ORF. Expression constructs encoding mCherry-tagged human Galactin3 (pLX304-mCherry-hGalectin3), GFP-tagged human LAMP1 (pCMV-hLAMP1-GFP) and mCherry-tagged human LAMP1 (pCMV-hLAMP1-mCherry) were kindly provided by Michael Hensel (University of Osnabrück, DE) and have been described in ( 41,42 ). Expression constructs encoding bacterial SMase fused to GFP-tagged LAMP1 were created by PCR amplification of DNA encoding residues 28-333 of Bacillus cereus SMase using pEF6-bSMase-V5-His and pEF6-bSMase D322A/H323A -V5-His 43 as templates, followed by cloning into BamHI and AgeI sites of pCMV-hLAMP1-GFP to yield LAMP1-bSMase-V5-GFP and LAMP1-bSMase dead -V5-GFP.…”
Section: Methodsmentioning
confidence: 99%
“…Expression constructs encoding cytoplasmic mKate-tagged EqtSM and EqtSol were created by PCR amplification followed by cloning into NheI and AgeI sites of mKate-LifeAct-7 (Addgene #54697), thereby replacing the LifeAct ORF. Expression constructs encoding mCherry-tagged human Galactin3 (pLX304-mCherry-hGalectin3), GFP-tagged human LAMP1 (pCMV-hLAMP1-GFP) and mCherry-tagged human LAMP1 (pCMV-hLAMP1-mCherry) were kindly provided by Michael Hensel (University of Osnabrück, DE) and have been described in ( 41,42 ). Expression constructs encoding bacterial SMase fused to GFP-tagged LAMP1 were created by PCR amplification of DNA encoding residues 28-333 of Bacillus cereus SMase using pEF6-bSMase-V5-His and pEF6-bSMase D322A/H323A -V5-His 43 as templates, followed by cloning into BamHI and AgeI sites of pCMV-hLAMP1-GFP to yield LAMP1-bSMase-V5-GFP and LAMP1-bSMase dead -V5-GFP.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work revealed that the SCV is prone to rupture, and damages compartments are targeted by membrane damage sensors and repair mechanisms such as galectins, sphingomyelinases, or the ESCRT machinery (Ellison et al, 2020; Göser et al, 2020; Paz et al, 2010; Thurston et al, 2012). We used an engineered version of equinatoxin II (EqtSM) as rapid membrane damage reporter that is binding cytosol-exposed sphingomyelin in damages endosomal membranes (Deng et al, 2016; Niekamp et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work revealed that the SCV is prone to rupture, and damages compartments are targeted by membrane damage sensors and repair mechanisms such as galectins, sphingomyelinases, or the ESCRT machinery (Ellison et al, 2020;Göser et al, 2020;Paz et al, 2010;Thurston et al, 2012).…”
Section: Trigger Invasion Enhances Membrane Damage At Nascent Scvsmentioning
confidence: 99%
“…Intestinal colonization by Salmonella is usually followed by invasion to the intestinal epithelium and macrophages. Salmonella has evolved a highly specialized membrane-bound compartment ( Salmonella -containing vacuole, SCV), which enables Salmonella to avoid the phagosome/lysosome of macrophage fusion for survival and multiplication [ 28 ]. Survival of Salmonella within macrophages plays an important role in the dissemination of Salmonella to the internal organs [ 29 ].…”
Section: Discussionmentioning
confidence: 99%